Kesetaraan Gender danPergulatan Status SosialWanita Bali dalamKonstelasiPolitikPraktis - Parmiti, Desak Putu (Universitas Pendidikan Ganesha, 2017)
This study aims to examine: the profile of Balinese women in practical political constellation, the draft model of gender-based political education, models for women in politics, scientific articles published in accredited journals. The research was analyzed by using descriptive qualitative analysis technique, and statistic analysis. The conclusions of this research, namely: 1) the role of political participation of women tends to be low. (2) Th e position and participation of women in political activity is highly marginalized. (3) The climate and communication patterns of family life, culture, official villages, and schools do not support the process of political education for indigenous women toÂ achieve improvement. (4) Indigenous village as the highest symbolism in the level of indigenous peoples structurally has not done any real activity in relation to political education on women. (5) The process of forming Indonesian civil society, in relation to the objectives and characteristics of indigenous peoples of indigenous Balinese villages, is quite relevant in creating a gender equality climate.